Optimizing Electronic Capture of Clinical Outcome Assessment Data in Clinical Trials: The Case of Patient-Reported Endpoints. (November 2015) - Fleming, Sarah; Barsdorf, Alexandra I.; Howry, Cindy; O'Gorman, Hannah; Coons, Stephen Joel
For a number of compelling scientific, operational, and regulatory reasons, the use of electronic data capture is becoming the preferred means of collecting clinical outcome assessment (eg, patient-reported outcome [PRO]) data in clinical trials. Electronic PRO (ePRO) data collection leverages screen-based technologies (eg, handheld devices, tablet computers, and web-based systems) and telephone-based (eg, interactive voice response) systems. Data collection is routinely either site based (ie, clinical study site) or field based (eg, subject's home, school, or workplace). While tablet computers are often used for site-based PRO data collection, handheld devices have become the mainstay for ePRO data capture in field-based settings. The data collection devices are usually provisioned to the sites or subjects by an ePRO system provider contracted by the clinical trial sponsor. With site-based data collection, study staff are responsible for ensuring subject compliance with the protocol-driven data collection procedures, whereas with field-based data collection, the subject is responsible for compliance with the data entry requirements and sites are accountable for remotely monitoring the data for compliance. In addition to site and subject compliance issues, technology-related factors must be anticipated in order to adhere to the electronic PRO data collection plan. The objective of this paper is to describe study site-, subject-, and technology-related factors that may lead to deviations from the planned electronic collection of PRO data (eg, defaulting to paper-based data collection) and to provide recommendations aimed at preventing potential problems or quickly resolving problems once they occur.